2016
DOI: 10.18355/xl.2016.09.02.90-102
|View full text |Cite
|
Sign up to set email alerts
|

Guide-interpreter’s language identity as an excursion discourse factor

Abstract: The paper deals with an excursion as a genre of oral communication which has its strict structure. The strategies of an excursion text are revealed and discovered. The authors consider the peculiarities of the guide-interpreter's language identity as a discourse factor of an excursion and analyze the specific features of the guideinterpreter's communicative actions in different parts of an excursion. The authors determine the influence of the guide-interpreter's professional and discourse pragmatically adequat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
5
0
2
Order By: Relevance
“…"Tourism discourse is multifunctional and suspects manysided research paradigms considering diverse genre peculiarity and the role which tourism plays in the modern society" [35]. However, the analysis of existing research has shown, that at the moment there are few studies considering the tourism discourse and tourism branding from the intercultural or translational viewpoint.…”
Section: Methodsmentioning
confidence: 99%
“…"Tourism discourse is multifunctional and suspects manysided research paradigms considering diverse genre peculiarity and the role which tourism plays in the modern society" [35]. However, the analysis of existing research has shown, that at the moment there are few studies considering the tourism discourse and tourism branding from the intercultural or translational viewpoint.…”
Section: Methodsmentioning
confidence: 99%
“…Great importance in the study of a human in language is being attached to the individual characteristics of the linguistic personality, the most important of which is gender. The gender defines the social, cultural and cognitive position of a human in the world where language plays a major role [1][2].…”
Section: Introductionmentioning
confidence: 99%
“…Этнокультурную специфику слов, не имеющих соответствия в переводе, можно передать в контексте всего поэтического произведения. Большое значение имеет лексическая сочетаемость слов в обоих языках и семантико-стилистическое соответствие [9].…”
unclassified